FIGHTING MODULE - KOMNATSKYI OLEKSAMDR LEONIDOVYCH; DMYTRENKO OLEKSANDR MYKOLAIOVYCH; HRECHKO VALERII VASYLIOVYCH; VOLKOV IHOR FEDOROVYCH (2006)
The fighting module has a rotary body arranged as two-level turret, automated gun with caliber not less than 30 mm, an anti-gun rocket complex, this is installed at the side wall of the turret, with possibility of variation of the angles of elevation, automated grenade discharge installed at the other side of the turret, machine-gun of caliber 7.62 mm coupled with automated gun, system of smoke grenades shooting, optical-television aiming-survey complex, supplementary sight, stabilizer of armament and infra-red headlight. As the run one uses the structure the upper part of which comprises of three rings, at that the middle ring is for installation of the minimal gap between the running tracks and the support balls, and the equilibration mechanism is made as a cylinder inside which there are two placed coaxially cylindrical springs and a rod, this by means of cable is connected to the outer ring of one of the bearings in which the armament block is installed. This utility model makes it possible to improve accuracy and grouping at automated shooting from arms the fighting module carries.